2010
DOI: 10.2116/analsci.26.375
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Injection On-line Electrochemical Separation/Determination of Ions Using a Two-Step Oil/Water-Type Flow Cell System

Abstract: A flow system for electrochemical separation and detection of ions was constructed by connecting two oil/water (O/W)-type flow cells, in which a long polarizable O/W interface was formed at the inner surface of a porous poly(tetrafluoroethylene) (PTFE) tube. Using this system, acetylcholine and choline ions, whose ion-transfer potentials are different by only 60 mV, could be separated and determined simultaneously. It was thus shown that the present flow system is promising for the electrochemical flow separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Online electrochemical separation of myoglobin and lysozyme and their simultaneous determination were performed with a flow cell system (Supporting Information Figure S1), which was composed of two online connected O/W-type flow cells, respectively, for separation and detection of proteins. The separation cell was prepared with a 50 cm long porous PTFE tube (1.0 mm inner diameter), whereas the detection cell with a 20 cm long one.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online electrochemical separation of myoglobin and lysozyme and their simultaneous determination were performed with a flow cell system (Supporting Information Figure S1), which was composed of two online connected O/W-type flow cells, respectively, for separation and detection of proteins. The separation cell was prepared with a 50 cm long porous PTFE tube (1.0 mm inner diameter), whereas the detection cell with a 20 cm long one.…”
Section: Methodsmentioning
confidence: 99%
“…Multivariate analysis for the foot potentials determined for different proteins with different surfactants successfully revealed that the protein selectivity should depend on surface properties of a protein molecule. Additionally, it was shown in principle that online electrochemical separation/determination of proteins could be performed using an O/W-type flow cell. …”
Section: Introductionmentioning
confidence: 99%
“…Osakai and coworkers used a microflow cell with a stationary organic phase stabilised below a hydrophilic dialysis membrane, to detect ions using pulsed amperometry [587]. Later, Kihara and co-workers constructed a two-step flow-cell system in view of applications to clinical samples [584], and Gohara and Osakai applied a similar two-step flow-cell system to the on-line electrochemical separation of acetylcholine and choline and their simultaneous determination [588].…”
Section: Practical Applicationsmentioning
confidence: 99%
“…The counter electrodes, CE, in W in the inner (10) and outer vessels (11) were platinum nets (100 mesh, 20 × 50 mm). The reference electrodes, RE, in W (12) and NB (13) in the inner vessel were silver-silver chloride electrode, SSE, and tetramethylammonium ion selective electrode, 20 TMAE, respectively. A stirring rod made of glass with 3 flat blades of 5 × 10 mm was placed at the center of the inner vessel, and the W | NB interface was stirred during electrolysis.…”
Section: Cells For Rapid Total Electrolysis At the W | O Interfacementioning
confidence: 99%
“…Though electrochemical principles applied to coulometric works performed so far have been redox reactions [1][2][3][4][5][6][7] except for the works introduced in this review, [8][9][10][11][12][13][14][15] the ion transfer reactions at the aqueous | organic solution, W | O, interface, [16][17][18] which have been investigated extensively during the last few decades as a field of electrochemistry, are expected to provide another principle applicable to coulometry. If coulometry expands its field to the interfacial ion transfers, the precise and absolute determination becomes possible not only for species that are easily oxidized or reduced in solutions, but also for those that are not easily oxidized or reduced.…”
Section: Introductionmentioning
confidence: 99%